Translating an ambitious vision into global transformation: the 2030 agenda for sustainable development - Markus Loewe; Nicole Rippin (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
On 26 September, the United Nations will adopt the `2030 Agenda for Sustainable Development', which includes 17 `Sustainable Development Goals' (SDGs). These Goals will replace the Millennium Development Goals and are meant to make international development transformative and sustainable. This ambition is reflected in their thematic scope which covers fundamental aspects of the social, the economic and the environmental dimensions of sustainable development. In addition, the SDGs are truly universal in nature, i.e. they constitute a challenge for all countries, including the most developed ones. Implementation of the 2030 Agenda will thus involve domestic policymakers as well as international cooperation and go beyond development policy. The list of indicators that is needed for making the goals and targets operational is expected for March 2016. Indicators will be fundamental for implementation, monitoring, reporting and evaluation. Therefore, a group of experts from the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE) have prepared detailed comments on all goals and the indicators that are currently under discussion. The result is an update of a draft version circulated earlier this year. The comments show how difficult it is to identify adequate indicators for all the goals in the new agenda. Some of them can be measured more easily while others are rather qualitative in nature so that it is difficult to measure progress in quantitative terms. In addition, some of the indicators under discussion are very complex with the effect that there is a risk that only experts are able to understand and remember them. Also, some goals lack specifications or a dead-line for achievement, or they are not yet measurable with the available data. And finally, some indicators cover just a small segment of what the respective goal is meant to achieve. With this review, we aim at providing an input for the debate on indicators and for the process of designing national strategies to implement the 2030 Agenda. The monitoring and review processes at the global, regional and national levels will be fundamental for measuring progress, and for adjusting policies. The introduction of the volume summarizes the achievements made by the adoption of a new agenda for sustainable development. It shows the advantages of the SDGs in comparison with the MDGs. The chapter after the introduction focusses on how the UN system can contribute to implementation, monitoring and review of the 2030 Agenda, and reflects on the possible shape of an accountability framework. The core of the discussion paper are chapters that review every SDG, its subordinate targets and its proposed indicators.
Keywords: 330; Agenda 2030; Regionale + globale + transnationale Governance